Near Earth space plasma monitoring under COST 296 - Jürgen Bremer (Annals of Geophysics, 2009)
This review paper presents the main achievements of the near Earth space plasma monitoring under COST 296 Action. The outputs of the COST 296 community making data, historical and real-time, standardized and available to the ionospheric community for their research, applications and modeling purposes are presented. The contribution of COST 296 with the added value of the validated data made possible a trusted ionospheric monitoring for research and modeling purposes, and it served for testing and improving the algorithms producing real-time data and providing data users measurement uncertainties. These value added data also served for calibration and validation of space-borne sensors. New techniques and parameters have been developed for monitoring the near Earth space plasma, as time dependent 2D maps of vertical total electron content (vTEC), other key ionospheric parameters and activity indices for distinguishing disturbed ionospheric conditions, as well as a technique for improving the discrepancies of different mapping services. The dissemination of the above products has been developed by COST 296 participants throughout the websites making them available on-line for real-time applications.